An admirable water for diseases of the luer, spleene, kidneis & all obstructions : Evaluation in the Titles of an Early Modern English Manuscript Recipe Book - Kaarrekoski, Sini (My University, 2018)
This study focuses on the evaluative function of recipe titles as evidenced in the early modern English manuscript recipe book MS V.a.619 (Folger Shakespeare Library, MS V.a.619). The study comprises of a structural analysis of the 535 recipe titles found in the manuscript, a lexical analysis of the evaluative adjectives found in the titles, and an analysis of intermingling between efficacy phrases and recipe titles. Evaluation is defined through the work of Thompson and Hunston as language use which reveals the opinions and value systems of the speaker or writer, and organizes discourse (Thompson and Hunston 2000, 6). Recipe titles are discussed in relation to the schema for the text type recipe formed by Fransisco Alonso-Almeida (Alonso-Almeida 2013). The key contributions of this study include additions to the pool of transcribed early modern English recipe texts, as Appendix 1 of this study is the first transcribed list of the contents of MS V.a.619 to exist. Additionally, this study adds to the schema formulated by Alonso-Almeida in terms of further exploring the evaluative function of recipe titles, and its importance in organising the discourse of early modern recipe collecting. This study also contributes to the study of MS V.a.619 in particular in revealing the opinions and values of the manuscript’s compiler.
Keywords: evaluation, manuscript studies, transcription, early modern English, recipe collections